2017
DOI: 10.3390/jcm6040046
|View full text |Cite
|
Sign up to set email alerts
|

Treatment and Prevention of Bleeds in Haemophilia Patients with Inhibitors to Factor VIII/IX

Abstract: The development of alloantibodies neutralising therapeutically administered factor (F) VIII/IX (inhibitors) is currently the most severe complication of the treatment of haemophilia. When persistent and at a high titre, inhibitors preclude the standard replacement treatment with FVIII/FIX concentrates, making patients’ management challenging. Indeed, the efficacy of bypassing agents, i.e., activated prothrombin complex concentrates (aPCC) and recombinant activated factor VII (rFVIIa), needed to overcome the ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
93
0
11

Year Published

2017
2017
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(108 citation statements)
references
References 95 publications
4
93
0
11
Order By: Relevance
“…FVII is an enzyme that belongs to the serine protease class [28, 35], whereas FVIII is a protein that is required for the activation of other coagulation factors [36, 37]. The results of the current study showed significant increases in the levels of FVII and FVIII associated with waterpipe and cigarette tobacco smoking.…”
Section: Discussionsupporting
confidence: 57%
“…FVII is an enzyme that belongs to the serine protease class [28, 35], whereas FVIII is a protein that is required for the activation of other coagulation factors [36, 37]. The results of the current study showed significant increases in the levels of FVII and FVIII associated with waterpipe and cigarette tobacco smoking.…”
Section: Discussionsupporting
confidence: 57%
“…ITI utilizes daily high‐dose intravenous FVIII infusions and can take months or even years to complete, often posing costs of >$1 000 000. During that time, bypass agents can restore haemostasis, but require careful dosing to prevent thrombosis, and increased potential for morbidity and mortality remain during that time (Rocino et al ., ). Progress has been made in defining the risk factors for inhibitor formation.…”
Section: Introductionmentioning
confidence: 97%
“…Over the past two to three decades, largely as a result of work aimed at preventing or stopping hemophilia-associated bleeding, several prohemostatic agents have been developed. Examples include prothrombin complex concentrates (PCCs or activated PCCs) and recombinant factor VIIa (rFVIIa), which are used to varying degrees to improve hemostasis and control bleeding [79]. …”
Section: Prohemostatic Molecules-overviewmentioning
confidence: 99%